Genotypic characterization of quinolone resistant-Escherichia coli isolates from retail food in Morocco. Issue 2 (1st February 2017) - Nayme, Kaotar; Barguigua, Abouddihaj; Bouchrif, Brahim; Karraouan, Bouchra; El Otmani, Fatima; Elmdaghri, Naima; Zerouali, Khalid; Timinouni, Mohammed
ABSTRACT: This study was conducted to assess the retail food as a possible vehicle for antimicrobial resistant, particularly quinolones resistant and pathogenic Escherichia coli . We determined the prevalence and characteristics of nalidixic acid (Nal) resistant E. coli isolates from diverse retail food samples. In all, 70 (28%) of 250 E. coli isolates studied were Nal-resistant E. coli and 91% of these were multi-drug resistant. Plasmid mediated quinolone resistance genes were identified in 32 isolates, including aac(6′)-Ib-cr (n = 16), qnrS1 (n = 11) and qnrB19 (n = 7). Mutations in gyr A and par C genes were detected among 80% of the isolates, and the isolates showed substitution Ser83-Leu and Asp87-Asn in gyrA and Ser80-Ile in parC. In addition, three different gene cassettes were identified ( aadA1, aadA7, aac(3)-Id ) in 18%. Virulence-associated genes stx1, eae, sfa, hlyA and stx2 were found in six (8%), three (4%), two (3%), three (4%) and three (4%) isolates, respectively. E. coli isolates of phylogenetic group A were dominant (64%, 45/70). Pulsed field gel electrophoresis revealed none epidemiological relationship between these isolates. The results of this work report the higher frequency of Nal-resistant E. coli isolates from Moroccan retail food samples including MDR and pathogenic isolates.